2018
DOI: 10.5935/abc.20180253
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relationship between Monocyte to High-Density Lipoprotein Ratio and Myocardial Bridge

Abstract: BackgroundAssessing the monocyte to high-density lipoprotein ratio (MHR) is a new tool for predicting inflamation, which plays a major role in atherosclerosis. Myocardial bridge (MB) is thought to be a benign condition with development of atherosclerosis, particularly at the proximal segment of the brigde.ObjectiveTo evaluate the relationhip between MHR and the presence of MB.MethodsWe consecutively scanned patients referred for coronary angiography between January 2013- December 2016, and a total of 160 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…It has been reported that increased MHR level was associated with systemic inflammation and MHR could be used as predictive marker of future cardiovascular disease. 20 , 32 , 33 , 34 , 35 To the best of the present authors’ knowledge, MHR has not yet been evaluated in patients with psoriasis. The current study revealed that MHR levels in the patient group were higher than those of the healthy controls, and that MHR values were positively correlated with PASI score.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that increased MHR level was associated with systemic inflammation and MHR could be used as predictive marker of future cardiovascular disease. 20 , 32 , 33 , 34 , 35 To the best of the present authors’ knowledge, MHR has not yet been evaluated in patients with psoriasis. The current study revealed that MHR levels in the patient group were higher than those of the healthy controls, and that MHR values were positively correlated with PASI score.…”
Section: Discussionmentioning
confidence: 98%
“… 20 , 32 However, HDL-C inhibits monocyte activities, impedes the transformation of monocytes to macrophages, and eliminates cholesterol from these cells, which leads to a restricted inflammatory response. 20 , 32 , 33 , 34 For this reason, it is reasonable to combine these two parameters into a single index (MHR) as an inflammatory marker. It has been reported that increased MHR level was associated with systemic inflammation and MHR could be used as predictive marker of future cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…A new prognostic factor in cardiovascular disease, the ratio of monocytes to high-density lipoprotein (MHR), has recently been recommended and could be used as an indicator of infl ammation. Elevated MHR levels were associated with cigarette smoking , obesity and muscular bridge diagnosed with coronary anjiography (4,14,15). The activation of monocytes and their differentiated forms into lipid-laden machropages plays a signifi cant role in the promotion of immune defense and also drives infl ammation and cardiovascular disease (1,3,9).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Arquivos Brasileiros de Cardiologia , Enhos et al. 5 proposed that a newly described tool for the assessment of inflammation and atherosclerosis - the relationship between monocytes and high-density lipoprotein (HDL), abbreviated as MHR (monocyte-to-HDL-cholesterol ratio) - could be associated with atherosclerosis in segments proximal to an MB. The authors studied 160 patients with MBs and without significant coronary lesions and observed that at a cut-off value of 13.55, the MHR was able to detect the presence of MBs with a 59% sensitivity, 65% specificity, and an area under the ROC curve of 0.687 (95% confidence interval 0.606-0.769, p < 0.001).…”
mentioning
confidence: 99%
“…The authors attributed this association to the occurrence of endothelial dysfunction and inflammation in patients with MB. 5…”
mentioning
confidence: 99%